ANALISIS YURIDIS PEMBATALAN PERJANJIAN KERJASAMA PEMBANGUNAN KEBUN KELAPA SAWIT ANTARA KOPERASI PERTANIAN SAWIT BUNGA IDAMAN DENGAN PT. PERDANA INTI SAWIT PERKASA DI DESA RANTAU BINUANG SAKTI (RBS) KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU DALAM PERKARA NO - Tamrin,; Almadison, (SUNGKAI, 2023)
Since the authority to grant oil palm plantation business permits was handed over to the Regency/City Government, the area of plantation business land in the Regency/City area has increased. Rokan Hulu Regency has the potential for large enough land for the development of oil palm plantations, but on the other hand, oil palm plantation business activities in Rokan Hulu Regency also have negative impacts, namely the occurrence of various conflicts between local communities and plantation companies both regarding community land and development of plantations for the community, conflicts over land between oil palm plantation companies. In the last 5 years, there have been conflicts between communities. The community demanded that the management of the Kopsa Bunda cooperative bring the community together with PT PIS II and the Rokan Hulu cooperative service. However, after a time the management of the Kopsa Bunda Cooperative instead carried out a credit agreement with Bank Mandiri Syariah and PT PIS II, the people of Rantau Binuang Sakti sued PT PIS II. The results of the research conducted are the cooperation agreement for the development of oil palm plantations between the Bunga Idaman Oil Palm Agricultural Cooperative and PT. Perdana Inti Sawit Perkasa in Desa RBS Kec. District fullness Rohul in Case No: 190/PDT.G/2021/PN.PBR was declared void. The form of settlement for the cancellation of the agreement is through settlement by bringing this case to court and the decision to cancel this agreement is decided by the Judge in court because it is through the Court that has the right and proves that something can be canceled.